The Effects of 16 Weeks of Exercise Training on Neutrophil Functions in Breast Cancer Survivors - Bartlett, David B.; Hanson, Erik D.; Lee, Jordan T.; Wagoner, Chad W.; Harrell, Elizabeth P.; Sullivan, Stephanie A.; Bates, Lauren C.; Alzer, Mohamdod S.; Amatuli, Dean J.; Deal, Allison M.; Jensen, Brian C.; MacDonald, Grace; et al. (Frontiers in Immunology, 2021)
Following therapy, breast cancer survivors (BCS) have an increased risk of infections because of age and cancer dysregulation of inflammation and neutrophil functions. Neutrophil functions may be improved by exercise training, although limited data exist on exercise and neutrophil functions in BCS. Sixteen BCS [56 (11) years old] completed 16 weeks of community-based aerobic + resistance exercise training and a 45-minute acute bout of cycling before (Base) and after (Final) the exercise training program. At Base and Final, we took BCS blood samples before (PRE), immediately after (POST), and 1 hour after (1Hr) acute exercise to determine neutrophil counts, phenotype, bacterial killing, IL-6, and IL-8 levels. Eleven healthy, age- and physical activity levels-matched women (Control) completed the acute bout of exercise once as a healthy response reference. BCS and Controls had similar Base PRE absolute neutrophil counts (p=0.801), but BCS had lower bacterial phagocytosis (p=0.035) and higher oxidative killing (p=0.005), lower CD16 (p<0.001), lower CXCR2 (p=0.032) and higher TLR2 (p=0.022) expression, while IL-6 (p=0.079) levels were marginally higher and IL-8 (p=0.316) levels similar. After 16 weeks of training, BCS Final PRE phagocytosis (p=0.146) and TLR2 expression (p=0.148) were no longer different from Controls. At Base, BCS phagocytic capacity and oxidative killing responses, CD16 and TLR2 responses, and IL-8 responses to acute exercise were different from Controls. After 16 weeks of training, BCS phagocytic capacity response, CD16 and TLR2 response, and IL-8 response to acute exercise were partially restored to responses approaching those observed in Controls. Following cancer therapy, BCS may have impaired neutrophil functions in response to an acute bout of exercise that are partially restored by 16 weeks of exercise training. The improved phagocytosis of bacteria in BCS may represent an intrinsic improvement in neutrophil functions consistent with a reduced risk of infectious disease.